Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

(cosecA+1).(1-sinA)=cosA.cotA
please can you answer this as fast as possible ​


Sagot :

Answer:

step by step below

Step-by-step explanation:

(cscA+1).(1-sinA)=cosA.cotA

(1/sinA +1).(1-sinA) = 1/sinA*(1 - sinA) + 1*(1-sinA)

                             = 1/sinA - 1  + 1 - sinA

                             = 1/sinA - sinA

                             = (1 - sin²A) / sinA

                             =cos²A / sinA

                             = cosA*cosA / sinA

                             =cosA*cotA

We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.